2018
DOI: 10.1038/s41420-018-0088-8
|View full text |Cite|
|
Sign up to set email alerts
|

Increased Krüppel-like factor 12 impairs embryo attachment via downregulation of leukemia inhibitory factor in women with recurrent implantation failure

Abstract: Recurrent implantation failure (RIF) caused by various etiological factors remains a challenge for fertility clinicians using assisted reproductive technology (ART) worldwide. Dysregulation of leukemia inhibitory factor (LIF) in the endometria of women with RIF is involved in impaired endometrial receptivity and embryo adhesion. However, the mechanism through which LIF expression is regulated in women with RIF is still poorly understood. Our previous study noted that the abnormally increased endometrial Krüppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…We also predicted that KLF12 is involved in the dioxin response, although there is no evidence in the literature. Therefore, it can be a prospective target to study further, as KLF12 is an essential regulator of embryo development, affecting the attachment of the embryo to the endometrial epithelium through the regulation of the leukemia inhibitory factor ( Lif ) gene [ 62 ]. KLF12 also plays a role in cancerogenesis and cell proliferation [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also predicted that KLF12 is involved in the dioxin response, although there is no evidence in the literature. Therefore, it can be a prospective target to study further, as KLF12 is an essential regulator of embryo development, affecting the attachment of the embryo to the endometrial epithelium through the regulation of the leukemia inhibitory factor ( Lif ) gene [ 62 ]. KLF12 also plays a role in cancerogenesis and cell proliferation [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we detected increased p-STAT3 expression in KLF12-deficient NK cells upon IL-21 stimulation, which correlated with greater IL-21mediated inhibition of proliferation. Similarly, overexpression of KLF12 in an endometrial adenocarcinoma cell line resulted in decreased p-STAT3 expression upon LIF stimulation, which inhibits cellular differentiation (42). The proliferative defect in KLF12deficient NK cells might be an intrinsic effect of p-STAT3 expression.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have shown that KLF12 regulates proliferation of many cancer cell lines. Overexpression of KLF12 in endometrial and lung cancer cell lines correlated with decreased apoptosis, increased cellular proliferation, and increased in vivo tumor growth (41)(42)(43). Conversely, downregulation of KLF12 resulted in a proliferative defect in multiple cancer cell lines (19,23,(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factor KLF12 is a member of KLFs family, which regulates gene transcription through binding to the CACCC sequence of target genes [31, 32]. Studies also showed that it can bind to the promoter regions of target genes and represses their expression [3235]. KLF12 acts to negatively regulate the expression of the decidual marker genes decidual prolactin and insulin like growth factor binding protein 1 in human endometrial stromal cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…KLF12 acts to negatively regulate the expression of the decidual marker genes decidual prolactin and insulin like growth factor binding protein 1 in human endometrial stromal cells [32]. KLF12 binds to the promoter region of leukemia inhibitory factor and directly represses its transcription [35]. While, KLF12 can directly activate the expression of early growth response protein 1 to promote the colorectal cancer growth [36].…”
Section: Discussionmentioning
confidence: 99%